(untitled) (BSAA arte, 2020)
The reign of Fernando VII supposed an attempt to consolidate the questioned political forms of the Ancien Régime. In this sense, the events linked to the royal deaths were very important, in which both ephemeral art and literature were put at the service of the monarchy. The funeral celebrations for the death of Queen María Isabel de Braganza were a good example of this attempt to consolidate the absolute monarchy at the end of its existence. The city of Burgos exemplifies very well this attempt to exalt Absolutism through the Baroque conceptual tradition and the Neoclassical forms.